An Organic Fraction of Oenothera rosea L'Her Ex. Aiton Prevents Neuroinflammation in a Rat Ischemic Model - Alejandro Costet-Mejía; Gabriela Trejo-Tapia; Itzel Isaura Baca-Ibarra; Aida Araceli Rodríguez-Hernández; Julio García-Hernández; Brenda Hildeliza Camacho-Díaz; Alejandro Zamilpa (MDPI AG, 2024)
Background: Oenothera rosea L'Her Ex. Aiton, presenting antioxidant and anti-inflammatory activities, is traditionally used to treat bruises and headaches and as a healing agent. This study aimed to investigate whether its organic fraction (EAOr) has neuroprotective properties against neuroinflammation in the context of ischemia/reperfusion. Methods: The chemical composition of EAOr was determined using HPLC techniques, and its neuroprotective activities were evaluated in a common carotid-artery ligation model for the induction of ischemia/reperfusion (I/R). The animals were supplemented with EAOR for 15 days. On the last day, the animals were rested for one hour, following which the common carotid-artery ligation procedure was performed to induce I/R. The neurological deficit was evaluated at 24 h after I/R using Bederson's scale, and the relative expression of inflammatory genes and structure of hippocampal neurons were analyzed at 48 h. Results: The chemical analysis revealed five major compounds in EAOr: gallic acid, rutin, ellagic acid, and glucoside and rhamnoside quercetin. EAOr prevented neurological deficit 24 h after I/R; led to the early activation of the AIF and GFAP genes; reduced Nfkb1, IL-1beta, Il-6 and Casp3 gene expression; and protected hippocampal neurons. Conclusions: Our findings demonstrate that EAOr contains polyphenol-type compounds, which could exert a therapeutic effect through the inhibition of neuroinflammation and neuronal death genes, thus maintaining hippocampal neurons.